Effect of postparturient oral calcium administration on serum total calcium concentration in Holstein cows fed diets of different dietary cation-anion difference in late gestation. (April 2018) - Afshar Farnia, S.; Rasooli, A.; Nouri, M.; Shahryari, A.; Khosravi Bakhtiary, M.; Constable, P.D.
Abstract: Minimizing the severity of post parturient hypocalcemia and the incidence of subclinical hypocalcaemia in multiparous dairy cows are important goals of the transition period. The primary objective of this study was to determine whether feeding an acidogenic ration in late gestation combined with oral CaCl2 administration after parturition improved calcium homeostasis when compared to feeding an acidogenic ration prepartum or oral CaCl2 administration postpartum alone. Forty-two Holstein dairy cows were randomly assigned to one of three groups of 14 cows. Group L were fed a low DCAD ration. Groups L + Ca and M + Ca were fed a low or moderate DCAD ration, respectively, and administered 50 g Ca as a CaCl2 solution at calving and 12 h later by ororuminal intubation in 500 mL of water. Mean serum [calcium] was lower immediately after parturition in group M + Ca (7.1 mg/dL) than group L + Ca (8.2 mg/dL). Oral CaCl2 administration increased mean serum [calcium] at 6 h after treatment in groups M + Ca (8.0 mg/dL) and L + Ca (8.7 mg/dL), but most of this increase had disappeared at 12 h after treatment. Group L + Ca had a higher serum [calcium] at time = 6 h and 12 h than the other two groups, and a higher serum [calcium] than group M + Ca at 1 and 2 days after treatment. We conclude that feeding an acidogenic ration in late gestation combined with oral CaCl2 administration provided a higher serum [calcium] at 6 and 12 h after parturition than feeding an acidogenic ration prepartum or oral CaCl2 administration postpartum alone.